الجرائم المرتكبة ضد الروهينغيا في ميانمار وآليات التصدي لها من منظور المحكمة الجنائية الدولية، Crimes Against The Rohingya In Myanmar And Mechanisms To Address Them From The Perspective Of The International Criminal Court - غبولي, منى; رؤوف, بوسعدية (Université de M'sila, 2020)
يهدف هذا المقال لتوضيح كيفية إعمال آلية التحقيق المتاحة أمام المحكمة الجنائية الدولية لوقف الإفلات من العقاب على الجرائم التي ارتكبتها ولازالت ترتكبها قوات دولة ميانمار ضد الإقلية المسلمة الروهينغية. حيث خلصنا إلى أنّ ما تقوم به هذا القوات عبارة عن جرائم دولية ثابتة في نظام المحكمة، وبالتالي يمتد اختصاص هاته الأخيرة للعقاب عليها رغم كون ميانمار دولة غير طرف فيها، وذلك لعدة أسباب تحقيقا للعدالة الجنائية الدولية. This article aims to illustrate how the investigative mechanism available to the International Criminal Court to stop impunity for crimes committed and still committed by Myanmar state forces against the Rohingya Muslim minority is enforced. We have concluded that the actions of these forces are international crimes that are consistent in the court system, and therefore the jurisdiction of the latter extends to punish them despite the fact that Myanmar is a non-party state, for several reasons in order to achieve international criminal justice.
Keywords: آلية التحقيق، المحكمة الجنائية، الانتهاكات الجسيمة، بورما. ; Investigative Mechanism, Criminal Court, Serious Violations, Burma.